Analisis Keuntungan Usaha Nasi Kuning "Ibu Jensy" di Kelurahan Bahu Kecamatan Malalayang Kota Manado (Profit Analysis of the Yellow Rice Business "Mrs. Jensy" in Bahu Village Malalayang Subdistrict Manado City) - Ricky Vincensius Dolang; Noortje M. Benu; Audrey J. M. Maweikere (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to find out how much profit Mrs. Jensy's yellow rice business makes in Bahu Village, Malalayang District, Manado City. This research was conducted from October to November 2021. The data collection in this research used interviews and documentation. The interview was conducted by directly interviewing the Nasi Kuning business owner as a respondent using a list of questions that had been prepared previously (questionnaire). Documentation is done by collecting data related to research both from relevant agencies and the internet. The data collected in this study were then analyzed using profit analysis using the Revenue Cost Ratio (R/C) analysis formula. The results showed that the yellow rice business "Ibu Jensy" in Bahu Village, Malalayang District, Manado City was profitable because the total revenue was Rp. 610,000 per day, the total cost is Rp. 441,614, so the profit obtained is Rp. 168,386 per day and the R/C value is 1.38.